Navigating the nexus of social appearance anxiety, learning autonomy, and collaborative dynamics in L2 acquisition: insights from Chinese university L2 learners - Tian, Weiqi; Liang, Jing; Zhao, Yani; Aolan, Mailihaba; Ge, Jingshen (Frontiers in Psychology, 2025)
IntroductionThis study examines the interconnected roles of social appearance anxiety, learning autonomy, and collaborative learning orientation in second language acquisition (SLA) among Chinese university students. Using Dynamic Systems Theory as a supplementary theoretical lens, it provides a dynamic interaction perspective for our study.MethodsThrough structural equation modeling, the research identifies the positive impact of learning autonomy and self-regulation on collaborative learning orientation and L2 proficiency though H1 was not supported.ResultsWe profoundly discussed this phenomenon within sociocultural context. The study advocates for pedagogical strategies that integrate real-world communication and alleviate social anxieties to enhance learning engagement.DiscussionLimitations include a cross-sectional approach, limited sampling size (N = 301), limited L2 assessment (CET-6). Prompting recommendations for broader demographic inclusion and refined measurements such as peer review for L2 oral capability etc. The findings stress the need for educational frameworks embracing both formal and informal learning contexts, underscoring autonomy’s pivotal role. This research provides actionable insights for stakeholders to create supportive environments, addressing psychological barriers and emphasizing interactive learning. Ultimately, it contributes to the theoretical advancement and practical improvement of L2 education.